DESCRIPTION OF A SILVICOLOUS TRECHINAE FROM CENTRAL MEXICO - BOLIVAR PIELTAIN, C (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1943)
Describes Paratrechus (subgen HYGRODUVALIUS) n sylvaticus from the humid localities of the Ajusco range (Central Mexico) between 9,000 and 10,000 ft A key is given for 7 spp of Paratrechus including 2 subgenera
AN ESC NAC CIENC BIOL
Keywords: DESCRIPTION, SILVICOLOUS TRECHINAE, CENTRAL MEXICO; CIENCIAS DE LA VIDA; ANTROPOLOGIA; ETNOLOGIA